Analisis Pengaruh Cutting Speed, Depth of Cut dan Feed Rate CNC Milling Terhadap Kekasaran Permukaan Aluminium 6061 Menggunakan Respons Surface Methodology (RSM) - Wahyudi Asri; Yudi Oktriadi; Erwansyah Erwansyah (Politeknik Manufaktur Negeri Bangka Belitung, 2026)
The development of modern manufacturing industries demands increased process efficiency and high-precision machining quality. One of the key factors determining product quality is surface roughness, particularly in Aluminum 6061, which is widely used in the automotive and precision manufacturing industries due to its light weight, strength, and corrosion resistance. An improper combination of machining parameters can reduce surface quality and process efficiency. Therefore, this study aims to analyze the effect of cutting speed, depth of cut, and feed rate on the surface roughness of Aluminum 6061 and to determine the optimal parameter combination. The analysis was conducted using the statistical method Response Surface Methodology (RSM). The results show that all three machining parameters significantly affect surface roughness, with the optimal combination obtained at a cutting speed of 70 m/min, feed rate of 318.3 mm/min, and depth of cut of 0.7 mm, producing the lowest surface roughness value of 0.224 µm (Ra).